Barriers to and enablers of insulin self‐titration in adults with Type 2 diabetes: a qualitative study. Issue 2 (8th October 2016) - McBain, H.; Begum, S.; Rahman, S.; Mulligan, K.
Abstract: Aims: To identify the barriers to and enablers of effective insulin self‐titration in people with Type 2 diabetes. Methods: A qualitative semi‐structured interview approach was used. Questions were structured according to the Theoretical Domains Framework, which outlines 14 domains that can act as barriers to and enablers of changing behaviour. Interviews were audio‐recorded and transcribed verbatim. The data were coded according to the 14 domains, belief statements were created within each domain, and a frequency count of the most reported barriers and enablers was then carried out. Analyses were conducted by two researchers, and discrepancies agreed with a third researcher. Results: A total of 18 adults with Type 2 diabetes took part in an interview. The majority were of South‐Asian ethnicity ( n = 8) and were men ( n = 12). Their mean age was 61 years old. The mean duration of diabetes was 16 years and time on insulin 9 years. Inter‐rater reliability for each of the domains varied (29–100%). The most frequently reported domains were Social Influence and Beliefs about Consequences; the least frequently reported were Optimism and Reinforcement. Interviewees reported receiving support to self‐titrate from a range of sources. Self‐titrating was perceived to have a range of both positive and negative consequences, as was not titrating. Conclusions: The findings highlight that those interviewed experienced a range of barriers and enablers when attempting to self‐titrate. Improved education and training when initiating insulin treatment among adults with Type 2 diabetes, and throughout their journey on insulin therapy could help identify and address these barriers in order to optimize self‐titration. What's new?: This study is the first to explore comprehensively the reasons people with insulin‐treated Type 2 diabetes struggle to self‐titrate their insulin, using an established theoretical framework. Important factors in facilitating self‐titration were support from healthcare professionals and family members, and having a target blood glucose reading and strategies to achieve this. Barriers to self‐titrating included difficulties experienced when at work or on holiday and concerns about the consequences of an increasing insulin dose. Holding strong but erroneous intentions to self‐titrate, suggested a lack of knowledge about self‐titration algorithms. Provision of educational resources and training when initiating insulin treatment in Type 2 diabetes and throughout treatment, in order to address these barriers and enhance these facilitators is vital.